2015
DOI: 10.1016/j.jcrs.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgically induced astigmatism between femtosecond laser and manual clear corneal incisions for cataract surgery

Abstract: Drs. Yoo and Donaldson are speakers for and consultants to Alcon Surgical, Inc., and Abbott Medical Optics, Inc. No other author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 19 publications
0
32
1
1
Order By: Relevance
“…2529 To make such an evaluation, it is mandatory to perform a vectorial analysis. 30 However, we decided not to check this in our patients because this topic has been widely studied in the international literature, 2529,31 and we could have added no new information.…”
Section: Discussionmentioning
confidence: 99%
“…2529 To make such an evaluation, it is mandatory to perform a vectorial analysis. 30 However, we decided not to check this in our patients because this topic has been widely studied in the international literature, 2529,31 and we could have added no new information.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are some evidences that recovery of visual acuity is faster with FLACS than manual capsulorhexis [12, 16]. Importantly, FLACS is considered to be associated with a similar or perhaps lower incidence of intra-operative and post-operative complications than conventional phacoemulsification [17, 18]. Moreover, most investigations indicate that changes in corneal endothelial cell density, corneal thickness and/or central retinal thickness are similar or smaller for FLACS than for manual capsulorhexis [1921].…”
Section: Introductionmentioning
confidence: 99%
“…In former studies, the SIA has been usually measured as the only refraction parameter that change with corneal incision, although changes in sphere power could be also induced by the incisions. Small increments of positive power in sphere have been reported[12] at 1-month follow-up, but no previous works have measured the long-term changes of both refraction components: sphere and astigmatism. On the other hand, corneal incisions also increase the values of the root mean square (RMS) of higher order aberrations (HOA), some previous studies[1518] have reported a significant change in trefoil aberration that increases as the corneal incision is larger[19,20].…”
Section: Introductionmentioning
confidence: 99%